IMPACT OF TOURISM VILLAGE DEVELOPMENT ON LOCAL COMMUNITY ECONOMY: CASE STUDY OF TETEBATU VILLAGE, LOMBOK - Kurniawan, Taufiq; Himni, Saleh Yahya; Sulhairi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Research on the impact of tourist village development on local community economy is a descriptive qualitative-based research. This research was conducted in Tetebatu Village, Lombok, Indonesia. The survey results revealed that the development activities of the tourist village of Tetebatu considered quite good, the main indicator is the average increase in tourist arrivals sizeable year-on-year. The readiness of local communities in terms of education, knowledge, and level of community involvement in the development of Tetebatu tourist village shows that the public has been sufficiently prepared to deal with potential impacts that arise. The level of development of tourism which generates high frequency level of interaction local communities and frequent travelers, which is an average of more than 5 times in the interaction per 3 months. The result shows that developing a tourist village brings a positive impact to the economic development of local communities in the Village of Tetebatu, including: the increase of public income; the increase of employment and business opportunities; the increase of ownership and control of local communities; the increase of government revenues through travel levy. While the indications of negative impact on the local economy in the form of rising prices of goods cannot be found.